1992
DOI: 10.1177/136140969200600104
|View full text |Cite
|
Sign up to set email alerts
|

Instrumentation and a Protocol for Quantification of Upper-Limb Movement of Children With and Without Cerebral Palsy in Two Sitting Positions

Abstract: Rehabilitation Engineering Department, Hugh MacMillan Rehabilitation Centre, 350 Rumsey Road&dquo; Toronto, Ontario, M4G 1 R8.The object of this paper is to present a preliminary report on an attempt to quantitatively analyze the effects of altered sitting positions on characteristics of an upperextremity reaching movement seen in children. A pilot study was conducted at the Hugh MacMillan Rehabilitation Centre, where the short-term effects of a horizontal (0°) and anteriorly-inclined (100) seat base on reachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Our study indicated that FW-tilting with foot-support was associated with a higher average velocity of reaching in all children with CP. Two other studies (Hadders-Algra et al, 2007;Reid Sochaniwskyj & Milner, 1992) evaluated the effect of FW-tilting on reaching velocity. Reid et al (1992) was unable to demonstrate an effect of 10°FW-tilting with foot-support on reaching velocity in Presented are the estimated marginal means based on the results from the (generalized) mixed effects models.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study indicated that FW-tilting with foot-support was associated with a higher average velocity of reaching in all children with CP. Two other studies (Hadders-Algra et al, 2007;Reid Sochaniwskyj & Milner, 1992) evaluated the effect of FW-tilting on reaching velocity. Reid et al (1992) was unable to demonstrate an effect of 10°FW-tilting with foot-support on reaching velocity in Presented are the estimated marginal means based on the results from the (generalized) mixed effects models.…”
Section: Discussionmentioning
confidence: 99%
“…To improve activities and participation of school-age children with CP often seating adaptations are used (Hadders-Algra & Carlberg, 2008;ICF-CY, WHO 2007;McNamara & Casey 2007;Stavness, 2006). From a theoretical perspective, the position of the pelvis is considered to be a crucial factor to achieve a seating position that is optimal for upper extremity function (Green and Nelham, 1991;McNamara & Casey 2007;Pope, 2002;Reid, Sochaniwskyj & Milner, 1992;Stavness, 2006). The idea is to achieve a seating position in which the line of gravity of the child's trunk and pelvis is close to the ischial tuberosities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 Outros autores verificaram, em seus estudos, que a inclinação do assento de 0 a 15 graus anterior, melhorou o controle postural e, fez com que as mãos das crianças ficassem livres para realizar atividades. [13][14][15] Certo estudo indicou que o uso da órtese abdutora e as inclinações do assento horizontal e inclinado anteriormente diminuem a atividade muscular dos membros inferiores e melhoram a função de membros superiores. 16 Vários estudos mostraram efeitos positivos na função de membros superiores, em uma inclinação de neutra a leve (10°) da cadeira como um todo.…”
Section: Introductionunclassified